2010
DOI: 10.1016/j.physa.2010.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Continuous opinion model in small-world directed networks

Abstract: In the compromise model of continuous opinions proposed by Deffuant et al, the states of two agents in a network can start to converge if they are neighbors and if their opinions are sufficiently close to each other, below a given threshold of tolerance ǫ. In directed networks, if agent i is a neighbor of agent j, j need not be a neighbor of i. In Watts-Strogatz networks we performed simulations to find the averaged number of final opinions < F > and their distribution as a function of ǫ and of the network str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 23 publications
(29 reference statements)
1
31
0
Order By: Relevance
“…For instance, simulations on square lattices and BA random graphs suggest that K depends not only on c, but also on N , when multiple opinion groups persist at equilibrium [26,45]. Simulations on WS random graphs indicate that K depends on both c and network structures, and that the presence of disorder (i.e., random "shortcut" edges) seems to have only a slight effect on convergence time T [43].…”
Section: The Deffuant Model On Various Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, simulations on square lattices and BA random graphs suggest that K depends not only on c, but also on N , when multiple opinion groups persist at equilibrium [26,45]. Simulations on WS random graphs indicate that K depends on both c and network structures, and that the presence of disorder (i.e., random "shortcut" edges) seems to have only a slight effect on convergence time T [43].…”
Section: The Deffuant Model On Various Networkmentioning
confidence: 99%
“…For WS random graphs, the study of the model has centered around opinion groups at equilibrium [43].…”
Section: The Deffuant Model On Various Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The second point is discussed below in Section 2.2.2. We have previously shown that these adaptations provide notable, and arguably more sociologically representative outcomes for opinion convergence modelling [28], as has subsequent work that also underlines the impact of both a continuous opinion convergence factor, and external determinants [6].…”
Section: Introductionmentioning
confidence: 75%
“…For example, the 'bounded confidence model' of opinion formation with continuous opinions has been studied extensively [1,2,3,4,5,6] . However, the impact of an adaptively changing social network within that framework has only recently been introduced, and it was shown, for example, that convergence to a small number of opinion clusters is more likely when links within the network change adaptively [4,5].…”
Section: Introductionmentioning
confidence: 99%